2007
DOI: 10.1007/s12010-007-9023-9
|View full text |Cite
|
Sign up to set email alerts
|

Biosensor for direct determination of fenitrothion and EPN using recombinant Pseudomonas putida JS444 with surface-expressed organophosphorous hydrolase. 2. Modified carbon paste electrode

Abstract: This paper reports a first microbial biosensor for rapid and cost-effective determination of organophosphorus pesticides fenitrothion and EPN. The biosensor consisted of recombinant PNP-degrading/oxidizing bacteria Pseudomonas putida JS444 anchoring and displaying organophosphorus hydrolase (OPH) on its cell surface as biological sensing element and a dissolved oxygen electrode as the transducer. Surfaceexpressed OPH catalyzed the hydrolysis of fenitrothion and EPN to release 3-methyl-4-nitrophenol and p-nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…66,68,106 The biosensor has been dened by Thevenot et al as "a selfcontained integrated device that is capable of providing specic quantitative or semi-quantitative analytical information using a biological recognition element (biochemical receptor), which is retained in direct spatial contact with a transduction element". 117 However, little scientic information regarding potential cell-based biosensors for detection of DLCs are available. Theoretically, biosensor techniques are categorized based on their bio-recognition elements being applied.…”
Section: Sensor Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…66,68,106 The biosensor has been dened by Thevenot et al as "a selfcontained integrated device that is capable of providing specic quantitative or semi-quantitative analytical information using a biological recognition element (biochemical receptor), which is retained in direct spatial contact with a transduction element". 117 However, little scientic information regarding potential cell-based biosensors for detection of DLCs are available. Theoretically, biosensor techniques are categorized based on their bio-recognition elements being applied.…”
Section: Sensor Technologymentioning
confidence: 99%
“…114 Biosensors include two major components: the transducer, which converts the event into an electronic signal and the bio-recognition element, which detects the specic contaminants. 72,117 The advantages of a whole cell-based biosensor for sediment or soil samples are its simple measurement, extraction and preparation techniques and low-cost instruments. These elements consist of DNA, antibodies, enzymes, biological receptors, and whole cells.…”
Section: Sensor Technologymentioning
confidence: 99%
“…Our group has developed several engineered strains displaying organophosphorus hydrolase (OPH) on the cell surface for the simultaneous hydrolysis of organophosphorous pesticides into p -nitrophenol and its subsequent conversion into electrochemically active intermediates [15,86]. By immobilizing these engineered cells onto a carbon paste electrode, different organophosphorus pesticides can be detected by measuring the corresponding electrooxidation current generated from these intermediates [90]. Similarly, Liu et al displayed xylose dehydrogenase (XDH) on the cell surface using the INP anchor for the detection of D-xylose, a compound of significant interest in genetics, human nutrition, food technology and pharmacology [87].…”
Section: Whole-cell Sensor Based On Extracellular Systemmentioning
confidence: 99%
“…Additionally, low relative CV% (n=6) showed excellent data reproducibility. Moreover, it was revealed that naturally existing compounds in serum did not cause significant interferences in (Table 2) [9,16,[22][23][24][25][26][27][28][29][30][31][32].…”
Section: Nanobiosensor Evaluationmentioning
confidence: 99%